1998
DOI: 10.1071/pp98043
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of quantum yield of PS II electron transport in Spirulina platensis by osmotic stress may be explained mainly by an increase in the proportion of the QB-non-reducing PS II reaction centres

Abstract: Modulated chlorophyll fluorescence and fluorescence induction kinetics were used to evaluate the PS II photochemistry in Spirulina platensis exposed to osmotic stress (0–0.8 M mannitol). Osmotic stress decreased the efficiency of excitation energy capture by open PS II reaction centres (Fv′/Fm′) and more significantly, decreased photochemical quenching (qP). Osmotic stress also decreased the maximal efficiency of PS II photochemistry (Fv/Fm). There was no significant change in non-photochemical quenching (qN),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…Fluorescence can provide insights into the ability of a plant to tolerate environmental stresses and into the extent to which those stresses have damaged the photosynthetic apparatus (Fracheboud et al 1999;Maxwell and Johnson 2000). Previous studies showed that severe desiccation led to a decrease in F v /F m (Chen and Hsu 1995) and UPSII (Lu et al 1998). In this experiment, UPSII and F v /F m of treated ramets disconnected from untreated ramets decreased with increasing soil water contrast, which showed that drought stress may increase under high water contrast.…”
Section: Discussionmentioning
confidence: 50%
“…Fluorescence can provide insights into the ability of a plant to tolerate environmental stresses and into the extent to which those stresses have damaged the photosynthetic apparatus (Fracheboud et al 1999;Maxwell and Johnson 2000). Previous studies showed that severe desiccation led to a decrease in F v /F m (Chen and Hsu 1995) and UPSII (Lu et al 1998). In this experiment, UPSII and F v /F m of treated ramets disconnected from untreated ramets decreased with increasing soil water contrast, which showed that drought stress may increase under high water contrast.…”
Section: Discussionmentioning
confidence: 50%
“…Vonshak et al (1988Vonshak et al ( , 1995Vonshak et al ( , 1996, Zeng and Vonshak (1998), Lu et al (1998 and Vonshak (1999, 2002) have shown that an increase in salt concentration leads to the decrease of the specific growth rate, photosynthetic efficiency, maximum rate of photosynthesis, phycobilin/Chl a ratio and PSII activity. Conversely, dark respiration activity, compensation points and PSI activity are increased.…”
Section: Discussionmentioning
confidence: 96%
“…In particular, photosynthetic adaptation against salt stress seems to be associated with the modification of energy collector complexes, antennas, or reaction centers. These modifications occur essentially in PS II (Vonshak et al 1996;Lu et al 1998Vonshak 1999, 2002). According to , enhanced respiration rates induce a decrease of energy transfer between phycobilisomes and PSII.…”
mentioning
confidence: 99%
“…In the cyanobacterium Arthrospira, many studies have investigated the effects of salinity stress, osmotic stress, and photoinhibition on photosynthesis and PSII photochemistry (Lu et al 1998;Lu and Vonshak 1999a;Zhang et al 2010). However, how high temperature (heat stress) affects photosynthesis in Arthrospira, especially in marine Arthrospira, remains to be elucidated further.…”
Section: Introductionmentioning
confidence: 98%